Islamic Education System for Elderly Islamic Boarding School in Cikarang, West Java - Chaedar, Muhammad Rusmin; Syah, Muhibbin; Ahmad, Nurwadjah (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2022)
Some of the elderly feel themselves as marginalized in social life, because of a decline in physical and mental abilities. So not a few who experience depression because of their weak faith. Therefore, intensive religious training is needed for them. One of the institutions for the religious development of the elderly is a boarding school which specifically fosters the elderly. This study aims to analyze the elderly education program at the Daarul Fikri Integrated Islamic Boarding School Â , Cikarang Bekasi, West Java about the basic values of the elderly pesantren; The purpose of the pesantren for the elderly; Characteristics of elderly Islamic boarding school students; Elderly boarding school program; Elderly islamic boarding school materials; Elderly boarding school method; Impact and evaluation of learning on religious understanding of the elderly. This study uses a qualitative approach with a descriptive method. The data collection technique uses observation, interview, and documentation techniques. Meanwhile, the analysis method goes through several stages, namely: data reduction, data presentation, and verification and drawing conclusions. The results of the study show: 1) The basic values of the elderly pesantren are support for the elderly to be able to live independently; 2) Islamic boarding schools for the elderly were established to accommodate the elderly who want to deepen their religious knowledge and seek inner peace; 3) Elderly students have special characteristics; 4) The elderly pesantren program is only held for one week for each generation; 5) The teaching materials in Islamic boarding schools for the elderly are the Qur'an, Islamic studies (Tawhid, Tafsir, Fiqh, akhlaq (islamic morality), tashihul worship, riyadloh / sports / natural meditation, worship guidance, dhikr, and morals. 6) The learning methods used in Islamic boarding schools for the elderly are discussions and lectures; 7) Elderly pesantren alumni feel an increase in religious insight and are diligent in establishing friendships. While the evaluation is focused on the implementation of the Islamic boarding school for the elderly.